Exposure assessment of pigs to methicillin-resistant Staphylococcus aureus (MRSA) in Benin City, Edo State, Nigeria - Joshua Atabo Odoh; Luka Ilu Mela; Esther Okolo; Gideon Ikechukwu Ogu (Aceh Journal of Animal Science, 2023)
The increasing data on methicillin-resistant Staphylococcus aureus (MRSA) is worrisome considering its public health relevance. Though, nutritionally rich and globally accepted like poultry products, pigs are potential asymptomatic carriers of S. aureus including methicillin-resistant strains, and thus, a serious threat to consumers. This study investigated one hundred and fifty (150) nasal swabs of pigs from fifteen (15) selected pig farms (PGF) within Benin City, Edo State, Nigeria, to assess their levels of exposure to S. aureus and MRSA carriage. Isolation, characterization, and identification of S. aureus and MRSA were done using Mannitol Salt Agar (Oxoid, UK) and Mannitol Salt Agar supplemented with 4µg/ml oxacillin, respectively. Antibiotic susceptibility patterns was done using disc diffusion protocols, while presence of MRSA mecA genes was characterised using PCR. Out of 150 samples analysed, a total of 45 S. aureus was recovered, yielding an overall prevalence of 30 % (45/150), with 28.9 % (13/45) MRSA. MRSA isolates were recovered from only 9 pig farms, with the highest from PGF14 (3 isolaes), followed by PGF 6 and PGF15 with 2 isolates each, and the rest 6 pig farms with just a single MRSA each. MRSA showed 100% resistance to penicillin (n=13) and lowest to vancomycin (n=5; 38.5 %). The MRSA isolates possessed mecA genes and were linked to the multi-drug resistance observed. Findings from this study suggest that some of the studied pigs are exposed to multi-drug resistant MRSA and thus a serious threat to the public. Wise use of antibiotics and well-coordinated surveillance programme is essential to combat this situation.